Model PBI - Nabiilah, Laila; Elvinawati; I Nyoman Candra (University of Bengkulu, 2023)
[The Influence of the Problem Based Learning (PBL) Model on Students' Analysis Ability on Buffer Solution Subjects]. This research is a pre-experimental research type aims to determine the effect of applying the Problem Based Learning (PBL) model on students' analytical abilities on buffer solution materials. The research was conducted at SMAN 4 Bengkulu City with a sample of class XI IPA 3, which consisted of 36 students. The instruments used in this study were analytical ability test sheets and observation sheets. From the research results obtained (1) the average pretest-posttest results experienced a significant increase, namely 7.67 to 64.43 from a maximum score of 100. The results of hypothesis testing using a t-test at the significance level of 0.05 obtained a Sig Value (2tailed) of 0.000 with a decision H0 is rejected and H1 is accepted. This shows that the problem-based learning model has an effect on students' analytical abilities, (2) the N-gain test results obtained an average of 0.61 in the medium category. The percentage increase in analytical skills on differentiating indicators is 66%, organizing indicators is 67%, and indicators of attributing are 51%.